From SHIQ and RDF to OWL: the making of a Web Ontology Language - Horrocks, Ian; Patel-Schneider, Peter F.; van Harmelen, Frank (Web semantics, 2003)
The OWL Web Ontology Language is a new formal language for representing ontologies in the Semantic Web. OWL has features from several families of representation languages, including primarily Description Logics and frames. OWL also shares many characteristics with RDF, the W3C base of the Semantic Web. In this paper, we discuss how the philosophy and features of OWL can be traced back to these older formalisms, with modifications driven by several other constraints on OWL. Several interesting problems have arisen where these influences on OWL have clashed.